2020
DOI: 10.3390/agronomy10030363
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Plant-Based Biostimulant Improves Plant Performances and Fruit Quality in Tomato Plants Grown at Elevated Temperatures

Abstract: Abiotic stresses can cause a substantial decline in fruit quality due to negative impacts on plant growth, physiology and reproduction. The objective of this study was to verify if the use of a biostimulant based on plant and yeast extracts, rich in amino acids and that contains microelements (boron, zinc and manganese) can ensure good crop yield and quality in tomato plants grown at elevated temperatures (up to 42 °C). We investigated physiological responses of four different tomato landraces that were cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 47 publications
6
72
0
3
Order By: Relevance
“…Different physiological and molecular responses of tomato to water limitation were recorded depending on microbial inocula, confirming the importance to characterize the optimal plant/beneficial microorganism genotype combination(s) to enhance plant resilience to water stress condition. Non-microbial plant biostimulants such as amino acids/peptides-based product and protein hydrolysates can also be considered an effective tools to improve the tolerance to a wide range of abiotic stresses: heat, hypotoxic, nutrient and salt stresses as well as combined environmental stresses [53,54]. The application of biostimulant based on plant and yeast extracts and containing amino acids, soluble peptides and vitamins improved the heat stress tolerance of four tomato landraces grown under Mediterranean conditions.…”
Section: The Role Of Non-microbial and Microbial Biostimulants In Abimentioning
confidence: 99%
See 1 more Smart Citation
“…Different physiological and molecular responses of tomato to water limitation were recorded depending on microbial inocula, confirming the importance to characterize the optimal plant/beneficial microorganism genotype combination(s) to enhance plant resilience to water stress condition. Non-microbial plant biostimulants such as amino acids/peptides-based product and protein hydrolysates can also be considered an effective tools to improve the tolerance to a wide range of abiotic stresses: heat, hypotoxic, nutrient and salt stresses as well as combined environmental stresses [53,54]. The application of biostimulant based on plant and yeast extracts and containing amino acids, soluble peptides and vitamins improved the heat stress tolerance of four tomato landraces grown under Mediterranean conditions.…”
Section: The Role Of Non-microbial and Microbial Biostimulants In Abimentioning
confidence: 99%
“…The application of biostimulant based on plant and yeast extracts and containing amino acids, soluble peptides and vitamins improved the heat stress tolerance of four tomato landraces grown under Mediterranean conditions. The biostimulant effects were associated to physiological and biochemical mode of actions, for example: (i) stronger antioxidant defense system; and (ii) maximal photochemical efficiency (F v /F m ) in leaves of the four tested tomato landraces [53]. Finally, Trevisan et al [54] demonstrated in a short-term trial that the application of a protein hydrolysates-based biostimulant was able to mitigate the detrimental effects of single (hypoxia, salt or nutrient deficiency) and multiple (nutrient stress + hypoxia or nutrient stress + salinity) stresses of hydroponically grown maize.…”
Section: The Role Of Non-microbial and Microbial Biostimulants In Abimentioning
confidence: 99%
“…Yeast extract (YE) 3% was prepared from active dry yeast (Saccharomyces cerevisiae) according to the modified method of Francesca et al [16] by dissolving amount of dry yeast in water followed by adding sugar (as a source of C and N) at a ratio of 1:1 and kept 24 hours in a warm place for activation before application on the plants. Yeast extract is rich in beneficial bioconstituents such as amino acids, peptides, phytohormones, vitamins, carbohydrates, trace elements, and other growth factors….etc., hence making it suitable for foliar application.…”
Section: Experimental Designmentioning
confidence: 99%
“…The improvement of plants growth in response to the foliar application of active dry yeast may be attributed to its nutritional contents of different nutrients, a relatively larger proportion of amino acids, higher percentage of peptides, phytohormones, higher values of vitamins, carbohydrates, trace elements, and other growth factors (Table 3). Many studies indicated that yeast has stimulatory effects on cell division, elongation, enlargement, chlorophyll formation, protein and nucleic acid synthesis [16] [25]. It was found that the simulative effect of yeast extract treatment can recover the reduction occurred in vegetative growth of leucaena plants which exposed to salinity stress [26].…”
Section: Vegetative Growth Parameters Of Garlicmentioning
confidence: 99%
“…Our findings support the idea that chlorophyll fluorescence parameters (i.e., Φ PSII or NPQ) and some leaf functional traits may be used as a tool to detect high temperatures-tolerant tomato cultivars.Plants 2020, 9, 508 2 of 16 and quality [5,6]. Tomato (Solanum lycopersicum), being an excellent source of health-promoting compounds, is one of the most important crops cultivated worldwide and its heat sensitivity varies among different genotypes [4,7,8]. Generally, the optimal temperature range for photosynthesis is considered to be between 25 • C and 30 • C [6].…”
mentioning
confidence: 99%